Opportunities and Challenges of Soft Skills Integration in the Curriculum of Islamic Religious Colleges: An Empirical Study at IAIN Kendari - Zulkifli Musthan; Dirman Dirman; Nasir Nasir (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2026)
The development of soft skills has become a crucial component of contemporary higher education, especially in terms of preparing graduates for social and professional life. Soft skills are closely linked to both employability and the development of moral character based on Islamic principles in the context of Islamic Higher Education Institutions (PTKI). The purpose of this study is to examine the opportunities, difficulties, and methods used in PTKI to help students develop their soft skills. Lecturers, faculty leaders, and students from various institutions, such as IAIN Kendari, Universitas Muhammadiyah Kendari, IAIN Madura, UIN Datokarama Palu, IAIN Pare-Pare, and IAIN Bone, participated in in-depth interviews, observations, and document analysis using a qualitative descriptive-analytical approach. The results show that classroom discussions, academic presentations, project-based learning, student organizations, and community service all contribute to the development of soft skills. They are still not systematically integrated into the curriculum, and cognitive outcomes are still given priority in evaluations, which limits the effectiveness of soft skills development in students. There are strategic opportunities for a more comprehensive PTKI education model by strengthening the integration of digital learning and Islamic values, which can enhance both soft skills and cognitive outcomes in students.